THE EFFECT OF THE ADDITION OF SNAKEHEAD FISH (Channa striata) PROTEIN CONCENTRATE ON THE QUALITY OF SEMPRONG CAKE - Angga Wijaya; Sukirno Mus; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was aimed to evaluate the effect of addition snakehead fish (Channa striata) protein concentrate on the quality of semprong cake. The method used was experimental and composed as completely randomized design (CRD). The treatment was the addition of snakehead fish protein concentrate, which was varied at 4 levels, (K0) original addition of snakedhead fish protein concentrate, addition of snakehead fish protein concentrate 5% (K1), addition of snakehead fish protein concentrate 10% (K2), addition of snakehead fish protein concentrate 15% (K3), snakehead fish protein concentrate addition percentage calculated by weight of rice flour formulation. The parameters used organoleptic evaluation, and proximate composition. The best treatment seen from organoleptic test K3 the addition with snakehead fish protein concentrate is 15%, with organoleptic value (K3 shape 3.56, K3 texture 3.48, K3 flavor 3.68, K3 taste 3.66), and proximate is water content K3 4.5%, protein content K3 21.62%, fat content K35.32%.Keywords: Channa striata, Fish Protein, Concentrate Semprong Cake, Quality Assessment